CNT based photoelectrodes for PEC generation of hydrogen: A review. (16th February 2017) - Rai, Snigdha; Ikram, Ashi; Sahai, Sonal; Dass, Sahab; Shrivastav, Rohit; Satsangi, Vibha R.
Abstract: Incorporation of carbon nanotubes (CNTs) with the semiconductors for their use as photoelectrode for efficient solar generation of hydrogen in photoelectrochemical (PEC) cell via splitting of water is a very recent and scorching topic of research. This review presents various perspective, challenges and comprehensive assessment of the worldwide research on the use of CNT-semiconductor hybrids in PEC cell. Different types of CNT based PEC systems investigated so far, methods of synthesis of CNT modified semiconducting photoelectrodes, their tailored properties beneficial for efficient production of hydrogen via PEC splitting of water along with critical analysis on the effectiveness of modified electrodes over unmodified have been presented in this review article. Highlights: Presents critical assessment of the worldwide research on CNT based PEC systems. CNTs act as very promising support for the semiconductors in PEC splitting of water. Factors like functionalization before hybrid preparation and use of optimal amount of CNTs are beneficial. Enhanced photoresponse of CNT based hybrids are mainly due to the conducting lane provided by CNTs. Various tailored properties of hybrids after CNT modification have been discussed.